Penerapan Layanan Aplikasi Perpustakaan Digital pada Perpustakaan Universitas Negeri Padang - Kurnia, Endi; Nabila, Jeihan (Lembaga Yasin AlSys, 2024)
This study aims to describe: (1) achievement of objectives in the implementation of digital library application services at the Padang State University Library; (2) integration in the implementation of digital library application services at the Padang State University Library; (3) adaptation to the application of digital library application services at the Padang State University Library.This research is a qualitative research with descriptive method. The research instrument used is an interview guideline. The data collection techniques used in this research are observation, interview, and the documentation. The data analysis are data collection, data reduction, data presentation, dan conclusions. Source triangulation was used to test the validity of the data in this study. The results of this study are as follows. First, the achievement of goals in the implementation of digital library application services at the Padang State University Library has not been maximized, limited membership quotas and the unavailability of applications on non-Android devices cause uneven access for users. Second, the integration of the implementation of digital library application services at the Padang State University Library is running quite well, the application is easy to use and also a different system from the traditional library system owned by Padang State University so that it is difficult to integrate the application service. Third, adaptation to the application of digital library application services at the Padang State University Library has not been maximized, the collections available in the application have not adjusted to the target users, in this case Padang State University students.